An unusual presentation of catastrophic antiphospholipid antibody syndrome in the background of sepsis - Hakeem, Sai C.; Oommen, Akash T.; Surendran, Sandeep; Madan, Sumanth (International Journal of Research in Medical Sciences, 2022)
A 59-year-old female presented with complaints of gangrenous changes over right ring finger and reduced renal output. She was in hypotension and had to be started on ionotropes. She also had acute kidney injury and was initiated on hemodialyis. Inspite of culture directed antibiotics and amputation of the necrotic region, her condition worsened. Considering the acute multisystem worsening, i.e., less than a week, concomitant autoimmune etiology was considered. Antiphospholipid antibodies were positive. Her tissue biopsy was suggestive of vasculitis. Hence the diagnosis of catastrophic antiphospholipid antibody syndrome (CAPS) was made. Quick recognition and appropriate treatment play a cornerstone in treatment of CAPS. She was pulsed with methylprednisolone and also treated with intravenous immunoglobulins and anticoagulants. She showed remarkable improvement and responded to the treatment. CAPS should always be kept as a differential in case of multisystem acute deterioration even in the background of sepsis. The treatment is a big challenge to physicians given the associated mortality rate if not briskly treated.